Answer:
x=-6, y=1
Step-by-step explanation:
Let's solve your system by substitution.
y=x+7;−2x−11=y
Step: Solve y=x+7 for y:
y=x+7
Step: Substitute x+7 for y in −2x−11=y:
−2x−11=y
−2x−11=x+7
−2x−11+−x=x+7+−x(Add -x to both sides)
−3x−11=7
−3x−11+11=7+11(Add 11 to both sides)
−3x=18
−3x/
−3
=
18/
−3 (Divide both sides by -3)
x=−6
Step: Substitute−6 for x in y=x+7:
y=x+7
y=−6+7
y=1 (Simplify both sides of the equation)
Answer:
x=−6 and y=1
If 7x+3=24, that means x would be 3 so if you take 5-4x then that would be -7.
Answer:
a. 144 cubic foot
b. 12 ft
c. 18 ft
Step-by-step explanation:
Let the volume of prism A be V_a
and that of prism b be V_b
ATQ, V_a + V_b= 432
also V_a= 0.5 V_b
⇒1.5 V_b= 432
= V_b= 432/1.5= 288 cubic feet
therefore V_a= 144 cubic feet
volume of prism= area of base×height = V_a
24×h = 144
⇒h= 12 ft
A_b= 2/3×24
⇒base area of prism B= 16 sq.ft
now 16×h_b= 288⇒h_b= 288/16= 18 ft
Answer:
4.0506100 x 10^-1
Step-by-step explanation:
Because all you need to do is move the decimal point to the right once, you write 10^-1 to show that to get back to the original number, you just multiply 4.0506100 by -0.1
So you divide 0.8 by 6.25 and your answer is 7.8125 and then you add 5.5 minutes of your other number and you get the answer of 13.3125